2010
DOI: 10.1038/ki.2009.498
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of H-Ras decreases renal fibrosis and myofibroblast activation following ureteral obstruction in mice

Abstract: Tubulointerstitial fibrosis is characterized by the presence of myofibroblasts that contribute to extracellular matrix accumulation. These cells may originate from resident fibroblasts, bone-marrow-derived cells, or renal epithelial cells converting to a mesenchymal phenotype. Ras GTPases are activated during renal fibrosis and play crucial roles in regulating both cell proliferation and TGF-beta-induced epithelial-mesenchymal transition. Here we set out to assess the contribution of Ras to experimental renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 46 publications
1
54
0
2
Order By: Relevance
“…A few recent papers show increased cell proliferation in TIF models and indicate that limiting cell proliferation could improve fibrosis development (45)(46)(47). Therefore, it might be interesting to speculate the role of cell proliferation in humans with TIF and in murine TIF models.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent papers show increased cell proliferation in TIF models and indicate that limiting cell proliferation could improve fibrosis development (45)(46)(47). Therefore, it might be interesting to speculate the role of cell proliferation in humans with TIF and in murine TIF models.…”
Section: Discussionmentioning
confidence: 99%
“…This is reminiscent of the EMT process that accompanies the switch from the anti-inflammatory to the profibrogenic role of TGF- observed during the progression of organ fibrosis. Interestingly, this switch is also associated with the reactivation of Snail1 expression and, likewise, forced Snail1 expression in normal kidneys is sufficient to generate EMT and fibrosis, leading to organ failure in transgenic mice (Boutet et al, 2006;López-Novoa and Nieto, 2009). It will be interesting to define the mechanism that prevents Snail1 upregulation in non-transformed adult hepatocytes.…”
Section: Snail1 Is Required For Tgf--mediated Emt In Hepatocytesmentioning
confidence: 99%
“…It will be interesting to define the mechanism that prevents Snail1 upregulation in non-transformed adult hepatocytes. Perhaps the susceptibility of cancer cells is related to the presence of activated Ras, which is crucial for the TGF--mediated induction of Snail1 expression and EMT in renal cells as well as in hepatic and pancreatic cell lines (Gotzmann et al, 2002;Peinado et al, 2003;Grande et al, 2009;Horiguchi et al, 2009). …”
Section: Snail1 Is Required For Tgf--mediated Emt In Hepatocytesmentioning
confidence: 99%
“…Tissue fibrosis is the common final outcome of a wide variety of chronic diseases, regardless of the initial causes (Liu, 2006;Boor et al, 2010;Zeisberg and Neilson, 2010). It is known that some signaling pathways have an important role in the occurrence and development of tissue fibrosis, such as Wnt/b-catenin (He et al, 2009), Notch (Bielesz et al, 2010), RasRaf-Mek (Grande et al, 2010), and the PI3K/Akt (phosphoinositide 3-kinase/protein kinase B) pathway (Niu et al, 2007). Recently, evidence has suggested that the Hedgehog (Hh) signaling pathway may be involved in fibrogenesis in multiple tissues Jung et al, 2011;Fabian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%